The discovery of the rare genus Epimicta Foerster (Hymenoptera: Braconidae) in China, with a description of a new species - Zheng, Min-Lin; Chen, Jia-Hua; Achterberg, C. Van (Zootaxa, 2013)
Epimicta sulciscutum sp. nov. fromHeilongjiang (North China) is described and illustrated. A key to species of the genus is provided.